Amir Khusrow Dihlavi's Advice Letter in the Preface of Masnavi Devalrani and Khizr Khan - AmirHossein Dowlatshahi; Mehdi Nourian (تاریخ ادبیات)
Devalrani and Khizr Khan is the description of the love of Khizr Khan Khalaji for Diveldi or Devalrani which Amir Khusrow Dihlavi (651-725 AH) composed in 715 AH. In a part of this Preface of Masnavi, Amir Khusrow has composed an advice letter addressed to the great sultan of the time, Alaeddin Mohammad Khalaji, whose important feature is the clarity of the poet's language and his audacity when advising the sultan. This article aimed to introduce the advice letter and to examine how its various mandatory and inhibitory topics were presented, elaborating on the reasons for the poet's choice of words in Sultan's sermon. To this end, after using the books of Indian history to delve into and identify the authoritative and callous personality of sultan’s Alaeddin Mohammad Khalaji, through examining the text of the advice letter as well as the characteristics of the poet described in various sources, the results indicate that the reasons for Amir Khusrow's explicit and brave truthfulness lies in his honesty and mysticism, his close relationship with Nizamuddin Auliya (the great mystic of the time), his high status at the royal court of Sultan Alaeddin, and the influence of Sanai’s recommendations on him.